Efficacy of thymosin-α-1 in patients with COVID-19: A systematic review and meta-analysis - Pu Wang; Changhong Wang; Da Chen (European Journal of Inflammation, 2023)
Objective To identify whether thymosin-α-1 (Tα1) is effective in patients with Coronavirus disease 2019 (COVID-19) and to determine a suitable population for Tα1 treatment. Methods We included studies with ≥10 cases and adults (aged ≥18 years) with laboratory-confirmed SARS-CoV-2 infection, data on mortality or length of hospitalization, disease severity, and study location, while excluded pregnant and breastfeeding women and minors. Publications were searched from November 1, 2019, to July 5, 2023, in six databases, including PubMed, Web of Science, Embase, Cochrane Library, China Knowledge Resource Integrated Database, and Wanfang Database. We separately utilized Newcastle-Ottawa Scale and Cochrane handbook methodology to evaluate risk of bias and used Review Manager (version 5.4, Cochrane Collaboration, Copenhagen, Denmark) to present and synthesize results. Relative risks (RR) and Standardized Mean Difference (SMD) with 95% confidence intervals (CI) were analyzed for dichotomous variables and continuous variables, respectively. Results Nine studies (participants = 5417) were included. No significant differences were found in mortality (nine studies; n = 5417; RR = 0.95; 95% CI: 0.56, −1.60; p = .84; I 2 = 90%) or length of hospitalization (four studies; n = 3688; SMD = 0.16; 95% CI: −0.38, −0.69; p = .57; I 2 = 96%) between patients with COVID-19 who did and did not receive Tα1. Participants were divided by the severity of the disease (serious and non-serious) and study location. Among the serious group, the incidence of death among patients who received Tα1 treatment was 0.67 times that of patients who did not receive Tα1 treatment (four studies; n = 1230; RR: 0.67; 95% CI: 0.58, −0.77; p < .00,001; I 2 = 0%). There was no significant difference in length of hospitalization between the groups (two studies; n = 410; SMD = 0.66; 95% CI: −0.06, −1.38; p = .07; I 2 = 87%). Among the non-serious group, compared to not having Tα1 treatment, receiving Tα1 treatment reduced hospitalization length (two studies; n = 3670; SMD = −0.28; 95% CI: −0.41, −0.14; p < .0001; I 2 = 51%), while no significant difference in mortality (three studies; n = 3775; RR = 1.06; 95% CI: 0.22, −5.03; p = .94; I 2 = 89%). Moreover, there was no significant difference between subgroups when divided by study locations (Studies within China: seven studies; n = 5263; RR = 1.14; 95% CI: 0.64, −2.04; p = .65; I 2 =92%; Studies outside of China: two studies; n = 154; RR = 0.41; 95% CI: 0.14, −1.24; p = .11; I 2 = 51%). Discussion For patients with serious types of COVID-19, Tα1 significantly decreased mortality, which supports the utilization of Tα1 in patients with severe and critical types of COVID-19. Moreover, regarding hospitalization length, patients with non-serious COVID-19 who used Tα1 reduced their hospitalization length compared to those that did not use Tα1. However, these results have high heterogeneity and limited generalizability.